2020
DOI: 10.1080/13678868.2020.1721982
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of social learning and learner outcomes in a massive open online course (MOOC): a healthcare sector case study

Abstract: Vol-10-issue-2-2016.pdf . 3. At the time of the research, Janet Wildman was employed by Horizons NHS Improving Quality Team 4. The authors acknowledge the contribution of M. Stella Martorana to the project reported in this paper. At the time of the HRD intervention and its evaluation discussed in this paper M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Drawing upon this theory of learning effects, [2] observe that if effective, virtual learning environments 'provide learners meaningful interactions with their professions and peers, foster a culture of learning, and support multiple learning styles.' With universities continuing to adopt the MOOC format of online education, [3] confirm empirically that only those students who participate in group exercises and discussions gain access to the developmental skills and social support necessary to improve their overall learning experience.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Drawing upon this theory of learning effects, [2] observe that if effective, virtual learning environments 'provide learners meaningful interactions with their professions and peers, foster a culture of learning, and support multiple learning styles.' With universities continuing to adopt the MOOC format of online education, [3] confirm empirically that only those students who participate in group exercises and discussions gain access to the developmental skills and social support necessary to improve their overall learning experience.…”
Section: Introductionmentioning
confidence: 80%
“…Such communities of practice (CoPs) integrate teacher moderators and student leaders in the negotiation of the learning process, requiring both productive collaboration and active engagement to improve the nature of these exchanges [10]. The CoP insights drawn from [3] reveal the social advantages of collaborative learning in MOOC courses and largescale educational environments where individual consideration is marginalised by the scope and integration of the classroom itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of social presence influences the quality of virtual interactions and outcomes. London & Hall (2011), Roberts and Sambrook (2014), Li and Wang (2013), Wu and Zhang (2014), Evans (2014Evans ( , 2019 and Anderson et al (2020) suggested that social networks and Web 2.0 tools could increase social presence in virtual business communications. The extent to which communication in a virtual environment can convey social presence will profoundly affect the quality of the digital travel experience, and the felt proximity wit people and places visited digitally.…”
Section: Interacting With Other Peoplementioning
confidence: 99%
“…Over the years, scholars have been exploring potentially effective tools and pedagogies to promote MOOC interactions, such as online forums ( Wise, 2018 ), social media ( Ostashewski et al, 2018 ; Anderson et al, 2020 ), and collaborative assignments ( Verstegen, 2018 ). However, study group, particularly “study group in blended mode” (i.e., face-to-face + online) remains relatively under-researched in the MOOCs literature.…”
Section: Introductionmentioning
confidence: 99%